Volunteers in Australian archives. Issue 2 (4th May 2017) - de Villiers, Annelie; Laurent, Nicola; Stueven, Christopher
Abstract: Why do volunteers choose to contribute thousands of unpaid hours per week to Australian archives? This paper presents the results of a nationwide web survey that provides insight into the demographics, motivations and experiences of volunteers in Australian archives. The findings provide a representative overview of formal volunteers in Australian archives, determining 'who' they are, the value of the contributions they provide and the level of training and support offered to them. This study is a continuation of existing discussions about volunteers in Australian archives and represents an opportunity for the development of stronger relationships with Australian archival volunteers and, through them, the communities our archives serve.